The Correlation of Television Show and Bullying Behavior in High School of Mahaputra in Makassar - Suryani Suryani; Andriani Andriani; Rosyidah Arafat (Faculty of Nursing, Universitas Hasanuddin, 2018)
Introduction: Bullying is an experience that occurs when the helplessness persecuted by the others behaviour and afraid of the repected bad behaviour and ill do it is repeated. One of causes bullying behavior is a television show, this can occur because television show that is presented is very diverse, so that school children is free to watch their favorite television show. This study aimed to determine the relationship between television show with bullying behavior in student of class XI and XII in SMA Maha Putra Makassar. Method: This study using cross sectional method. The total study populations 130 and samples are 98 respondents with purposive sampling technique. Data analyzed were using the Chi-Square. Result: In this study showed that there is no relationship between television show with bullying behavior in student of class XI and XII in Maha Putra Senior High School Makassar. Conclusions: Level bullying dominant is low level with the bullying often is verbal bullying, and program often that watched is soap opera. Therefore, they are expected to do more introduce of bullying to students.